Tuning the cationic interface of simple polydiacetylene micelles to improve siRNA delivery at the cellular level. Issue 11 (1st October 2019) - Hoang, Minh-Duc; Vandamme, Marie; Kratassiouk, Gueorgui; Pinna, Guillaume; Gravel, Edmond; Doris, Eric
Abstract : Polydiacetylene micelles, bearing different cationic head groups, were systematically investigated for their ability to efficiently deliver functional siRNAs to cells. Abstract : Polydiacetylene micelles were assembled from four different cationic amphiphiles and photopolymerized to reinforce their architecture. The produced micelles were systematically investigated, in interaction with siRNAs, for intracellular delivery of the silencing nucleic acids. The performances of the carrier systems were rationalized based on the cell penetrating properties of the micelles and the nature of their cationic complexing group, responsible for efficient siRNA binding and further endosomal escape.